Comparison of kinesthetic sense among yoga sports and normal - Ketheeswaran, K.; Gopinath, V. (Selvam College of Physical Education, 2012)
Yoga is the science of right living and as such is intended to be incorporated in daily life, it works on all aspects of the person: the physical, vital, mental, emotional, phychic and spiritual. Kinesthetic is deals with the sense of movement. The receptors for kinetic sensibility are embedded in muscle joints and tendons. The Efficient kinesthesis is essential to the skillful performance of definite manual work and also success in sports and yoga practice. Kinesthetic awareness is a major means of learning. The presence of kinesthetic sense has often been considered as one of the factors contributing to the ability of an individual learns an activity or a skill. For the purpose 30 subjects were selected, group - I (n=10) Yoga Department, group – II (n=10) Physical Education and group – III (n=10) normal students from Annamalai University and their age ranged between 18 – 24 years. They were tested on selected kinesthetic variables (distance perception jump and shuffle board distance perception). The data was analysed by ANOVA and scheffes post hoc test. In the all the cases 0.05 level of confidence was fixed to test the significance. The results of the study shows that yoga students better than other two groups.
Keywords: Embedded; Phychic; Kinetic; Awareness